Production of dual functional carbon material from biomass treated with NaOH for supercapacitor and catalyst. Issue 5 (1st July 2021) - Özarslan, Saliha; Atelge, Muhammed Raşit; Kaya, Mustafa; Ünalan, Sebahattin
Abstract: In this research, tea factory waste (TFW), an organic biomass source, was used as a metal free basic catalyst for the production of hydrogen from NaBH4 by methanolysis. In the preparation of the catalysts, tea factory wastes taken from the tea factory and released during tea production were used. For the production of H2 from NaBH4 by methanolysis, TFW was pre‐treated with different base materials (KOH, NH4 Cl, and NaOH). Tests have been made on different mixing ratios, combustion temperatures, and durations for catalyst optimization by selecting the base with the highest hydrogen yield. Hydrogen production efficiency was recorded as 2832.2 and 6560.8 mL min −1 g −1 at 30°C and 60°C, respectively. The activation energy of the catalyst was defined as 18.07 kJ mol −1 . Characterization of TFW catalyst was examined by SEM‐EDX, XRD, and FT‐IR analysis. When the obtained data were evaluated and some studies available in the literature were considered, it was concluded that tea factory wastes, which are a biomass resource, can be used in catalyst production. The capacitance value of the electrode was computed as 8 to 12.9 F g −1 .